Updated measurement of decay-time-dependent CP asymmetries in D0→K+K− and D0→π+π− decays - Aaij, Roel; Archilli, Flavio; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2020)
A search for decay-time-dependent charge-parity (CP) asymmetry in D0→K+K− and D0→π+π− decays is performed at the LHCb experiment using proton-proton collision data recorded at a center-of-mass energy of 13 TeV, and corresponding to an integrated luminosity of 5.4  fb−1. The D0 mesons are required to originate from semileptonic decays of b hadrons, such that the charge of the muon identifies the flavor of the neutral D meson at production. The asymmetries in the effective decay widths of D0 and ¯D0 mesons are determined to be AΓ(K+K−)=(−4.3±3.6±0.5)×10−4 and AΓ(π+π−)=(2.2±7.0±0.8)×10−4, where the uncertainties are statistical and systematic, respectively. The results are consistent with CP symmetry and, when combined with previous LHCb results, yield AΓ(K+K−)=(−4.4±2.3±0.6)×10−4 and AΓ(π+π−)=(2.5±4.3±0.7)×10−4.
Gesehen am 21.02.2020
*LHCb Collaboration: R. Aaij, F. Archilli, P. D'Argent, S. Bachmann, D. Berninghoff, M. Borsato, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, H. Malygina, J. Marks, S. Neubert, A. Piucci, N. Skidmore, S. Stemmle, U. Uwer, A. Zhelezov [und 891 weitere Personen]
Im Titel sind die Zahl "0" und das Zeichen "+" und "-" hochgestellt